Cytokine Expression in Human Osteoblasts After Antiseptic Treatment: A Comparative Study Between Polyhexanide and Chlorhexidine. (1st February 2015) - Röhner, Eric; Hoff, Paula; Gaber, Timo; Lang, Annemarie; Vörös, Pauline; Buttgereit, Frank; Perka, Carsten; Windisch, Christoph; Matziolis, Georg
ABSTRACT Purpose/Aim of the study: Chlorhexidine and polyhexanide are frequently used antiseptics in clinical practice and have a broad antimicrobial range. Both antiseptics are helpful medical agents for septic wound treatment with a high potential for defeating joint infections. Their effect on human osteoblasts has, so far, not been sufficiently evaluated. The aim of this study was to investigate the activating potential of polyhexanide and chlorhexidine on inflammatory cytokines/chemokines in human osteoblasts in vitro. Materials and Methods: Human osteoblasts were isolated and cultivated in vitro and then treated separately with 0.1% and 2% chlorhexidine and 0.04% polyhexanide as commonly applied concentrations in clinical practice. Detection of cell structure and cell morphology was performed by light microscopic inspection. Cytokine and chemokine secretion was determined by using a multiplex suspension array. Results: Cell shrinking, defective cell membrane, and the loss of cell adhesion indicated cell damage of human osteoblasts after treatment with both antiseptics was evaluated by using light microscopy. Polyhexanide, but not chlorhexidine, caused human osteoblasts to secrete various interleukins (1β, 6, and 7), interferon γ, tumor necrosis factor α, vascular endothelial growth factor, eotaxin, fibroblast growth factor basic, and granulocyte macrophage colony-stimulating factor as quantified by multiplex suspension array. Conclusions: Both antiseptics induced morphological cell damage at an optimum exposure between 1 and 10 min. But only polyhexanide mediated a pronounced secretion of inflammatory cytokines and chemokines in human osteoblasts. Therefore, we recommend a preferred usage of chlorhexidine in septic surgery to avoid the induction of an inflammatory reaction.